Assessment of Total Fat and Fatty Acids in Walnuts Using Near-Infrared Hyperspectral Imaging - Nogales-Bueno, Julio; Baca-Bocanegra, Berta; Hernández-Hierro, José Miguel; Garcia, Raquel; Barroso, João Mota; Heredia, Francisco José; Rato, Ana Elisa (Frontiers in Plant Science, 2021)
“Persian” walnut (Juglans Regia L.) is one of the most consumed tree nuts in the world. It is rich in several bioactive compounds, with polyunsaturated and monounsaturated fatty acids (PUFA and MUFA) appearing at high concentrations. Walnut consumption protects against cardiovascular, carcinogenic and neurological disorders. The fatty acid profile has usually been determined by gas chromatography, a reliable and robust tool, but also complex, polluting and time consuming. In this study, near infrared hyperspectral imaging has been used for the screening of total fat, MUFA, PUFA, saturated and individual fatty acids in walnuts. Five different walnuts varieties have been considered and modified partial least square (MPLS) regressions have been performed. The standard errors of prediction (SEP) in external validation (ranged from 2.12% for PUFA to 13.08% for MUFA) suggest that hyperspectral imaging can be a reliable tool for controlling these parameters in a simple, non-destructive and environmentally friendly way.